2010
DOI: 10.28945/1128
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Comparative Study of Student Perceptions in Online Education

Abstract: This paper, a subset of a larger experimental longitudinal study, compared students' perceptions over-time of an e-learning environment. This paper includes an investigation of eight beliefs corresponding to three main categories; course activities, interactions with instructors, and interactions with other students. Both face-to-face and online students' perceptions were measured over eight years, in a course designed using Chickering's Seven Principles of Good Practices and the constructivist approach to cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…While expressing concerns about rise in online courses (Tanner et al, 2006), graduates also grew to accept online education as being equal to or better than traditional FTF (Perrault et al, 2008). Over 8 years, students' perceptions changed as course activities and student interactions with others were satisfied (Mortagy & Boghikian-Whitby, 2010).…”
Section: Student Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While expressing concerns about rise in online courses (Tanner et al, 2006), graduates also grew to accept online education as being equal to or better than traditional FTF (Perrault et al, 2008). Over 8 years, students' perceptions changed as course activities and student interactions with others were satisfied (Mortagy & Boghikian-Whitby, 2010).…”
Section: Student Characteristicsmentioning
confidence: 99%
“…Studies report student distress with online learning with ambiguous instructions (Perreault et al, 2008). Research favors research-based validated online frameworks with benchmarks and favors a student-centered model (Mortagy & Boghikian-Whitby, 2010). Students choosing to take online courses typically cite flexibility and convenience (Horspool & Lange, 2012;Perreault et al, 2008), the ability to self-control the learning environment (Armstrong, 2011), avoiding a commute to campus, and work demands (Horspool & Lange, 2012).…”
Section: Program Characteristicsmentioning
confidence: 99%
“…Using the same survey instrument as a previous study, results indicated that as business students took more courses, their perceptions of the OL environment improved, and their perception that OL courses were more difficult than traditional classes increased (Fish & Snodgrass, 2014). Therefore as shown in many studies (Dobbs et al, 2009;Mortagy & Boghikian-Whitby, 2010;Perreault et al, 2008), as students experience in the OL environment increases over time, their perceptions improve with increasing exposure to the OL environment. Prior research indicates that students need to complete at least 5 OL courses before they perceive that they learn more in the OL environment than FTF (Dobbs et al, 2009)…”
Section: Literature Reviewmentioning
confidence: 81%
“…As students take more courses, studies evaluating student's perceptions of OL courses demonstrate an increasing acceptance of OL as being equal to or better than FTF (Dobbs et al, 2009;Fish & Snodgrass, 2014;Mortagy & Boghikian-Whitby, 2010;Perreault et al, 2008;Tanner et al, 2003). This study sought to explore when this change occurred as students' perceptions over a single course were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation